Smart Governance: Integrasi Teknologi dan Teori Pemerintahan dalam Pelayanan Publik - Togala, Risman; Arsalim, Arsalim; Parisu, Chairan Zibar L. (Universitas Pahlawan Tuanku Tambusai, 2025)
This paper discusses the integration of digital technology and governance theory in an effort to realize effective and adaptive public services. The concept of Smart Governance does not only focus on the use of information technology, but also collaborative communication, transparency, and accountability in public policy making. Through a qualitative case study approach, this article examines the implementation of smart governance in several cities in Indonesia, including Bandung, Semarang, and Palu. The results of the study show that the application of technology such as e-Government and artificial intelligence has made a significant contribution to improving the quality of public services, although there are still challenges in terms of regulation, digital literacy, and infrastructure. By referring to the theory of governance and good governance, this paper recommends strategies for strengthening local regulations, HR training, and increasing collaboration between stakeholders.